Estimated Cumulative Incidence of Wisdom Tooth Extractions in Privately Insured US Patients - Schroeder, Alan R.; Newman, Thomas B.; Girod, Sabine; Hashemi, Sepehr; Häberle, Astrid D. (Frontiers in Dental Medicine, 2022)
Objective To determine the cumulative incidence and predictors of third molar (3M, “wisdom teeth”) extractions in the United States. Methods We retrospectively analyzed a US private dental insurance claims database to create a Kaplan-Meier curve for the cumulative incidence of 3M extractions and used Cox proportional hazards to assess associations between sex, geographic region, and extractions. Results Between 2007 and 2016, by age 25, ~80% of patients underwent ≥1 tooth extraction and an estimated 50% of patients underwent ≥1 3M extraction. Factors associated with 3M extractions included female sex (adjusted hazard ratio [aHR] 1.08, 95% CI 1.07–1.08) and residence in the West (aHR 1.82, 95% CI 1.81–1.85) or South (aHR 1.5, 95% CI 1.49–1.51) geographic regions as compared to the Northeast. Conclusion 3M extractions are likely the most common surgery performed in US adolescents and young adults. Significant geographic variation suggests that elucidation of the indications for this common procedure is a public health priority.